Analisis Ketersediaan Prasaran Dan Fasilitas Penunjang Pengembangan Objek Wisata Pantai Liang Kecamatan Salahutu Kabupaten maluku Tengah - Fahrudin T Meturan; Muhammad Idris Taking; Rudi Latief (Journal of Urban Planning Studies, 2021)
FAHRUDIN T. METURAN (Analysis of the Availability of Infrastructure and Support Facilities for the Development of Tourism Objects in Liang Beach, Kecamtan Salahutu, Central Maluku RegencyThis research aims to identify the availability of infrastructure and facilities to support the development of Liang Beach tourism objects and to find out the direction for developing Liang Beach tourism objects.As for this study, using several analysis tools including qualitative descriptive analysis, namely to describe the factual conditions in the field in the form of existing conditions that occur in the tourist area of ​​Liang Beach. While the weighting analysis is used to determine the potential of each existing indicator to assess the ability of a tourist attraction that can be developed. From these two analyzes, it can be determined the direction of the development of tourism object areas in a descriptive qualitative manner. The results of the analysis are three (3) zones, namely the Core Zone, the Support Zone and the Buffer Zone. Keywords: Development, Coastal Tourism